Gene Expression and Fatty Acid Profiling in Longissimus thoracis Muscle, Subcutaneous Fat, and Liver of Light Lambs in Response to Concentrate or Alfalfa Grazing - Dervishi, Elda; González-Calvo, Laura; Blanco, Mireia; Joy, Margalida; Sarto, Pilar; Martin-Hernandez, R.; Ordovás, Jose M.; Serrano, Magdalena; Calvo, Jorge H. (Frontiers in Genetics, 2019)
A better understanding of gene expression and metabolic pathways in response to a feeding system is critical for identifying key physiological processes and genes associated with polyunsaturated fatty acid (PUFA) content in lamb meat. The main objective of this study was to investigate transcriptional changes in L. thoracis (LT) muscle, liver, and subcutaneous fat (SF) of lambs that grazed alfalfa (ALF) and concentrate-fed (CON) slaughtered at 23 kg and using the Affymetrix Ovine Gene 1.1 ST whole-genome array. The study also evaluated the relationship between meat traits in LT muscle, including color, pigments and lipid oxidation during 7 days of display, α-tocopherol content, intramuscular fat (IMF) content and the fatty acid (FA) profile. Lambs that grazed on alfalfa had a greater α-tocopherol concentration in plasma than CON lambs (P < 0.05). The treatment did not affect the IMF content, meat color or pigments (P > 0.05). Grazing increased the α-tocopherol content (P < 0.001) and decreased lipid oxidation on day 7 of display (P < 0.05) in LT muscle. The ALF group contained a greater amount of conjugated linoleic acid (CLA), C18:3 n-3, C20:5 n-3, C22:5 n-3, and C22:6 n-3 than did the CON group (P < 0.05). We identified 41, 96 and 4 genes differentially expressed in LT muscle, liver, and subcutaneous fat, respectively. The most enriched biological processes in LT muscle were skeletal muscle tissue development, being the genes related to catabolic and lipid processes downregulated, except for CPT1B, which was upregulated in the ALF lambs. Animals grazing alfalfa had lower expression of desaturase enzymes in the liver (FADS1 and FADS2), which regulate unsaturation of fatty acids and are directly involved in the metabolism of n-3 PUFA series. The results found in the current study showed that ingesting diets richer in n-3 PUFA might have negative effects on the de novo synthesis of n-3 PUFA by downregulating the FADS1 and FADS2 expression. However, feeding diets poorer in n-3 PUFA can promote fatty acid desaturation, which makes these two genes attractive candidates for altering the content of PUFAs in meat.